2023
DOI: 10.2196/42087
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Habitual Use of Wearable Health Devices Among Middle-aged Individuals With Metabolic Syndrome Risk Factors in South Korea: Cross-sectional Study

Abstract: Background Prevention of the risk factors for metabolic syndrome (MetS) in middle-aged individuals is an important public health issue. Technology-mediated interventions, such as wearable health devices, can aid in lifestyle modification, but they require habitual use to sustain healthy behavior. However, the underlying mechanisms and predictors of habitual use of wearable health devices among middle-aged individuals remain unclear. Objective We investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…Consistent with previous research (19,(49)(50)(51)(52), this study demonstrated that the public's performance expectancy, social influence, hedonic motivation, and habit perception directly and positively influence women's continued intention to use women's health WeChat public accounts. This suggests that the UTAUT2 model exhibits consistency in explaining the influencing factors of user's continued intention to use health WeChat public accounts targeting different audiences and content.…”
Section: Impact Of the Utaut2 Model On The Continued Intention To Use...supporting
confidence: 89%
See 3 more Smart Citations
“…Consistent with previous research (19,(49)(50)(51)(52), this study demonstrated that the public's performance expectancy, social influence, hedonic motivation, and habit perception directly and positively influence women's continued intention to use women's health WeChat public accounts. This suggests that the UTAUT2 model exhibits consistency in explaining the influencing factors of user's continued intention to use health WeChat public accounts targeting different audiences and content.…”
Section: Impact Of the Utaut2 Model On The Continued Intention To Use...supporting
confidence: 89%
“…If the content of the public account is exciting and enjoyable, allowing users to experience fun, they may have a higher acceptance of the health WeChat public account and be more willing to read its content in the long term ( 53 ). The hedonic motivation for acceptance and intention to use a product has also been explained in other mobile health technologies ( 50 52 ). This study also indicated that habit can promote the continued intention to use women’s health WeChat public accounts.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Factors, such as PE, EE, and FCs, were found to be positively influencing the adoption of similar mHealth technologies for diabetes management in previous research [33,34]. However, recent studies focusing on the influencing factors of wearable devices for diabetes and other conditions management have observed that although PE, EE, and BI were high; FCs, PPR, SI, and PI were found to be of low or negative impact on the intentions to adopt wearable devices [35][36][37][38]. Issues, such as privacy and security concerns, have significantly influenced the user's trust in wearable devices, which had an indirect impact on the adoption of wearable devices.…”
Section: Discussionmentioning
confidence: 93%